Calidad de vida en 2001 - Velázquez, Guillermo Ángel (2020)
The adjusted definition of an "objective" quality of life index is neither simple nor universally valid. Based on our own research and on previous works widely discussed in specific areas, we will use, on the one hand, the socio-economic dimensions of education, health, housing and, on the other hand, the environmental risks and the attributes of attraction of the landscape, to determine levels of quality of life of the Argentine population in the year 2001. By using census information, as well as other statistical sources and selected scientific works.